The Individual and Community in African Traditional Religions - Sundermeier, Theo (LIT Verlag Münster, 1998)
"The writer has done a careful, scholarly and sensitive and very positive and fair study of African religion, with particular reference to the individual and community. Theo Sundermeier lets Africa speak for itself and on its own terms and in its own categories. The concluding chapter is a necessary reading for all who would be on mission, who would seek to live the ecumenical imperative and care to ensure that the pursuit of a religion does not result in dehumanization and degradation and marginalization of the other person." Rev. Canon Prof. John S. Pobee, World Council of Churches, Geneva/Switzerland "This book treats the subject of African religions in a creative and interesting way emphasizing that these religions are genuine, authentic expressions of religiosity on a par with other religions including the so-called world religions. The author provides an excellent account of the nature interdependence between individual, community, society and the natural order, an interdependence which these religions symbolize and express in ritual and belief. Likewise the essentially personal nature of power as conceived in African culture is thoughfully and interestingly analysed. There are many other thought provoking ideas and interpretations in this volume including the deconstruction of the commonly held notions of the distinction between witchcraft and magic. This is a most worthwhile contribution to the study of Africa's traditional religions and I am convinced all those with an interest in Africa who read it will gain much therefrom". Professor Peter B Clarke, Professor of the History and Sociology of Religion in the University of London at King's College, and formerly Professor of African History at the University of Ibadan, Nigeria. Theo Sundermeier is Professor of the History of Religion and Missiology at the Ruprecht-Karls-Universität Heidelberg. translated by Elaine Griffiths, Eleanor Jackson
Keywords: Religion / Comparative Religion